An index for enabling socially inclusive digital innovation processes in food, land, and water systems - Opola, Felix Ouko; Langan, Simon J.; Singaraju, N.; Arulingam, Indika; Schumann, C.; Jacobs-Mata, Inga; Nortje, Karen (CGIAR Initiative on Digital Innovation, 2023)
Currently metrics for assessing digital inclusivity focus on evaluating the outcomes of digital innovation rather than the process of developing such innovations. Digital inclusivity has five different dimensions, spanning both technical and social aspects, and therefore requires a holistic approach to attain. We propose a digital inclusivity index as a holistic and standard guideline for enabling digital inclusivity in food land and water systems. Since formal research and development is skewed towards the Global North, such an index may embody the perspectives and interests of organisations based in the Global North, and will therefore require testing, validation and co-development with stakeholders based in the Global South.